Exploring the Use of Mobile-Assisted Language Learning (Mall) for EFL Learning at A Junior High School in Cirebon - shofwaturrahmah, shofwaturrahmah; Rohadi, Tedi; Yavani, Zakky (STIT Buntet Pesantren Cirebon, 2023)
Mobile phone is very important for EFL teaching and learning. In education, there are several ways in which mobile phones can increase foreign language education. Then, this is the digital era students are very familiar with using mobile phones, gadgets, and other mobile applications that are English this requires teachers to master various skills. Teachers must be creative in the teaching and learning process, for example, using technology such as mobile phones. This study aims to explore how the teachers apply MALL (Mobile Assisted Language Learning) and what difficulties teachers face in implementing MALL (Mobile Assisted Language Learning) for EFL Learning at a Junior High School in Cirebon. This research was conducted by using a case study method in Junior High School. The subjects of this study were English teachers who had used MALL (Mobile mobile-assisted language Learning) in their learning; The results of this study show that the use of Mobile Assisted Language Learning is related to using MALL devices Laptops, and Mobile Phones as teaching media, and applications used by teachers, WhatsApp, Telegram, YouTube, Google Classroom, Zoom, Jamboard, Padlet, Live Worksheet, and Quizizz in EFL learning. The difficulties that teachers face are Classroom Management, Connectivity and Internet, Distraction, and Time management.